All solid state battery

JP7639348B2Active Publication Date: 2025-03-05TOYOTA JIDOSHA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021003099
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-12
Publication Date
2025-03-05
Estimated Expiration
2041-01-12

AI Technical Summary

Benefits of technology

【0008】 本開示の全固体電池によれば、固体電解質層と正負極層との界面接触性の劣化を抑制し、自己放電時の電圧低下を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639348000002
    Figure 0007639348000002
  • Figure 0007639348000003
    Figure 0007639348000003
  • Figure 0007639348000001
    Figure 0007639348000001
Patent Text Reader

Abstract

To provide an all-solid-state battery which can suppress a voltage drop during self-discharge by preventing degradation in interfacial contact between a solid electrolyte layer and positive / negative electrode layers.SOLUTION: An all-solid-state battery comprises a negative electrode, a solid electrolyte layer, and a positive electrode which are laminated in this order. The solid electrolyte layer has: a first solid electrolyte layer adjacent to the negative electrode; and a second solid electrolyte layer located between the first solid electrolyte layer and the positive electrode. The first solid electrolyte layer has a Young's modulus lower than that of the second solid electrolyte layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to all-solid-state batteries. [Background technology]

[0002] In the field of lithium ion secondary batteries, development of all-solid-state batteries with a solid electrolyte (hereinafter also referred to as SE) is underway in order to improve safety compared to non-aqueous electrolyte batteries. All-solid-state lithium ion secondary batteries (hereinafter also referred to as all-solid-state batteries) have an electrode body in which a positive electrode, a solid electrolyte layer, and a negative electrode are laminated in this order, and charge and discharge are performed by Li ions moving back and forth between the positive electrode and the negative electrode via the solid electrolyte. Therefore, there is a demand for an all-solid-state battery that is highly reliable and has excellent charge and discharge cycles in which the occurrence of short circuits is suppressed even when the battery is repeatedly charged and discharged.

[0003] As a technique related to such all-solid-state batteries, Patent Document 1 discloses an all-solid-state battery using an alloy-based active material as an all-solid-state battery negative electrode suitable for achieving both high cell volume energy density and excellent capacity retention. Patent Document 2 discloses a solid electrolyte layer of an all-solid-state battery that includes a powder compact part formed from a powder of a first solid electrolyte, and a surface deposition film formed by depositing a second solid electrolyte by a vapor phase method on at least one surface of the positive electrode side or the negative electrode side, thereby suppressing dendrite growth of metallic lithium and preventing internal short circuit of the battery. Patent Document 3 discloses a solid electrolyte sheet in which a solid electrolyte layer with a porosity of 10% or less and an easily destructible layer with a porosity of 15% or more are laminated. Furthermore, Patent Document 4 discloses an all-solid-state battery that uses a silicon-based material as an anode active material, in which an interelectrolyte void surrounded by a solid electrolyte is present in at least a region formed of a solid electrolyte in the anode layer, and the void ratio of the interelectrolyte void in the anode layer is 3.4 vol% or more and 29.6 vol% or less when the total volume of the anode layer is taken as 100 vol%. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-054720 A [Patent Document 2] JP 2009-301959 A [Patent Document 3] JP 2020-107594 A [Patent Document 4] JP 2019-185897 A Summary of the Invention [Problem to be solved by the invention]

[0005] When the negative electrode layer contains Si (silicon) as in the all-solid-state battery of Patent Document 1, the negative electrode layer expands and contracts with the intercalation of Li (lithium) ions during charging and discharging, and stress and strain may be transmitted to the solid electrolyte layer. The transmission of stress and strain to the solid electrolyte layer may cause gaps and cracks at the interfaces between the solid electrolyte layer and the positive and negative electrode layers, deteriorating the interfacial contact between the solid electrolyte layer and the positive and negative electrode layers, causing an electrical short circuit, and increasing the voltage drop during self-discharge (natural discharge).

[0006] In view of the above circumstances, an object of the present disclosure is to provide an all-solid-state battery that can suppress deterioration of interfacial contact between a solid electrolyte layer and a positive or negative electrode layer and suppress a voltage drop during self-discharge. [Means for solving the problem]

[0007] As one means for solving the above problems, the present disclosure provides an all-solid-state battery in which a negative electrode, a solid electrolyte layer, and a positive electrode are laminated in this order, the solid electrolyte layer having a first solid electrolyte layer adjacent to the negative electrode and a second solid electrolyte layer located between the first solid electrolyte layer and the positive electrode, and the first solid electrolyte layer has a smaller Young's modulus than the second solid electrolyte layer. Effect of the Invention

[0008] According to the all-solid-state battery of the present disclosure, deterioration of the interfacial contact between the solid electrolyte layer and the positive and negative electrode layers can be suppressed, and a voltage drop during self-discharge can be suppressed. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a diagram illustrating an all-solid-state battery 100 according to an embodiment. [Diagram 2] 1 shows the results of cell resistance measurement and self-discharge evaluation in Examples 1 to 8 compared to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the present invention will be described with reference to one embodiment of an all-solid-state battery 100. Note that the following embodiments are merely examples of the present invention, and the present invention is not limited to the following embodiments.

[0011] (All-solid-state battery) FIG. 1 is a cross-sectional view in the lamination direction for explaining an all-solid-state battery 100 according to one embodiment. As shown in FIG. 1, the all-solid-state battery 100 includes an electrode body 60 in which a positive electrode 20, a solid electrolyte layer 30, and a negative electrode 40 are laminated in this order. The solid electrolyte layer 30 includes a first solid electrolyte layer 31 adjacent to the negative electrode 40, and a second solid electrolyte layer 32 disposed between the first solid electrolyte layer 31 and the positive electrode 20. The positive electrode 20 includes a positive electrode current collector 22 and a positive electrode layer 21 formed on the positive electrode current collector 22, and the negative electrode 40 includes a negative electrode current collector 42 and a negative electrode layer 41 formed on the negative electrode current collector 42. The electrode body 60 defines an essential structure for constituting an all-solid-state battery. Therefore, the number of electrode bodies 60 may be one, but may be multiple from the viewpoint of improving battery performance. In addition, components may be shared between one electrode body 60 and another electrode body 60. Furthermore, in FIG. 1, the exterior body that houses the electrode assembly 60 and the like are omitted.

[0012] Hereinafter, each component of the electrode body 60 will be described. In this specification, the term "particle size" refers to the particle size at 50% cumulative value (D50 )

[0013] <Positive electrode> The positive electrode 20 has a positive electrode current collector 22 and a positive electrode layer 21 formed on the positive electrode current collector 22, and the positive electrode layer 21 is disposed in contact with the second solid electrolyte layer 32. Note that, although the positive electrode layer 21 is disposed only on one side between the positive electrode current collector 22 and the second solid electrolyte layer 32 in FIG. 1, it may be formed on both sides of the positive electrode current collector 22.

[0014] {Positive electrode layer} The positive electrode layer 21 includes at least a positive electrode active material. The positive electrode active material may be a known positive electrode active material applicable to all-solid-state batteries. For example, lithium-containing composite oxides such as lithium cobalt oxide and lithium nickel oxide may be used. The particle size of the positive electrode active material is not particularly limited, but is in the range of 5 to 50 μm, for example. The content of the positive electrode active material in the positive electrode layer 21 is in the range of 50% by weight to 99% by weight, for example. The surface of the positive electrode active material may be covered with an oxide layer such as a lithium niobate layer, a lithium titanate layer, or a lithium phosphate layer.

[0015] The positive electrode layer 21 may optionally include a solid electrolyte. Examples of the solid electrolyte include an oxide solid electrolyte and a sulfide solid electrolyte. A sulfide solid electrolyte is preferable. An example of an oxide solid electrolyte is Li7La3Zr2O 12 , Li 7-x La3Zr 1-x Nb x O 12 , Li3PO4, Li 3+x PO 4-x N x (LiPON), etc. Examples of sulfide solid electrolytes include Li3PS4, Li2S-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Si2S-P2S5, Li2S-P2S5-LiI-LiBr, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5-GeS2, etc. The content of the solid electrolyte in the positive electrode layer 21 is not particularly limited, but is, for example, in the range of 1% by weight to 50% by weight.

[0016] The positive electrode layer 21 may optionally include a conductive assistant. The addition of the conductive assistant can improve the electronic conductivity of the positive electrode layer. Examples of the conductive assistant include carbon materials such as acetylene black, ketjen black, and vapor grown carbon fiber (VGCF), and metal materials such as nickel, aluminum, and stainless steel. The content of the conductive assistant in the positive electrode layer 21 is not particularly limited, but is, for example, in the range of 0.1% by weight to 10% by weight.

[0017] The positive electrode layer 21 may optionally include a binder. The binder is not particularly limited as long as it is chemically and electrically stable, and examples thereof include rubber-based binders such as butadiene rubber (BR), butylene rubber (IIR), acrylate butadiene rubber (ABR), and styrene butadiene rubber (SBR); fluorine-based binders such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polytetrafluoroethylene (PTFE); olefin-based binders such as polypropylene (PP) and polyethylene (PE); cellulose-based binders such as carboxymethyl cellulose (CMC); and polyimide. The content of the binder in the positive electrode layer 21 is not particularly limited, and is, for example, in the range of 0.1% by weight to 10% by weight.

[0018] The thickness of the positive electrode layer 21 is not particularly limited and may be appropriately set according to the desired battery performance, for example, in the range of 0.1 μm to 1 mm.

[0019] {Positive electrode current collector} The positive electrode current collector 22, which collects the positive electrode active material contained in the positive electrode layer 21, may be made of metal foil, metal mesh, or the like. Metal foil is particularly preferred. Examples of metals constituting the positive electrode current collector 22 include stainless steel, aluminum, nickel, iron, copper, titanium, and carbon. The thickness of the positive electrode current collector 22 is not particularly limited and may be the same as that of a conventional one. For example, it is in the range of 0.1 μm to 1 mm.

[0020] {Preparation of the positive electrode} The method for producing the positive electrode 20 is not particularly limited, and the positive electrode 20 can be produced by a known method. For example, the material constituting the positive electrode layer 21 is mixed with a solvent to form a slurry, and the slurry is applied to the surface of the positive electrode current collector 22 (which may be the second solid electrolyte layer 32) as the base material by a wet method such as a doctor blade method, a die coating method, or a gravure method, and then dried to produce the positive electrode 20.

[0021] <Solid electrolyte layer> The solid electrolyte layer 30 is a separator layer formed between the positive electrode 20 and the negative electrode 40, and has a first solid electrolyte layer 31 adjacent to the negative electrode 40, and a second solid electrolyte layer 32 disposed between the first solid electrolyte layer 31 and the positive electrode 20.

[0022] {First solid electrolyte layer} The first solid electrolyte layer 31 is a stress relaxation layer that relaxes the propagation of stress and strain to the solid electrolyte layer due to expansion and contraction of the negative electrode layer during charge and discharge, and contains a solid electrolyte and a binder. The solid electrolyte may be of the same type as the solid electrolyte used in the positive electrode layer 21. The content of the solid electrolyte in the first solid electrolyte layer 31 is in the range of 60% by weight to 97% by weight, for example.

[0023] The binder may be the same as that used in the positive electrode layer 21, but is preferably a rubber-based binder such as butadiene rubber (BR), butylene rubber (IIR), acrylate butadiene rubber (ABR), or styrene butadiene rubber (SBR). The Young's modulus of the first solid electrolyte layer 31 is set to be smaller than that of the second solid electrolyte layer 32 described below. In order to make the Young's modulus of the first solid electrolyte layer 31 smaller than that of the second solid electrolyte layer 32, the binder content in the first solid electrolyte layer 31 is preferably larger than that in the second solid electrolyte layer 32, and is, for example, in the range of 3% by weight to 40% by weight. In addition, from the viewpoint of suppressing an increase in cell resistance, the binder content in the first solid electrolyte layer 31 is preferably 30% by weight or less. Here, the "Young's modulus" is also called the modulus of longitudinal elasticity, and is a constant calculated from the relationship between elongation and force when stretched and compressed in one direction, and when the Young's modulus is small, it means that deformation occurs greatly in response to external stress, that is, it is soft. One method for measuring this is compression stress-strain measurement testing.

[0024] The thickness of first solid electrolyte layer 31 is, for example, in the range of 3 μm to 15 μm from the viewpoint of suppressing self-discharge with a minimum increase in resistance. Furthermore, the ratio of the thickness of first solid electrolyte layer 31 to the total thickness of solid electrolyte layer 30 formed from first solid electrolyte layer 31 and second solid electrolyte layer 32 is preferably in the range of 0.1 to 0.5, from the viewpoint of suppressing a voltage drop during self-discharge.

[0025] {Preparation of the first solid electrolyte layer} The method for producing the first solid electrolyte layer 31 is not particularly limited, and the first solid electrolyte layer 31 can be produced by a known method. For example, the materials constituting the first solid electrolyte layer 31 are mixed with a solvent to form a slurry, and the slurry is applied to the surface of a substrate by a wet method such as a doctor blade method, a die coating method, or a gravure method, and then dried to produce the first solid electrolyte layer 31. The substrate can be of the same type as the positive electrode current collector 22.

[0026] {Second solid electrolyte layer} The second solid electrolyte layer 32 includes a solid electrolyte and a binder. The solid electrolyte may be of the same type as the solid electrolyte used in the positive electrode layer 21. The content of the solid electrolyte in the second solid electrolyte layer 32 is in the range of 50% by weight to 99% by weight, for example.

[0027] The binder may be the same as that used in the positive electrode layer 21, but is preferably a fluorine-based binder such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE), or polyimide. The Young's modulus of the second solid electrolyte layer 32 is set to be greater than that of the first solid electrolyte layer 31. In order to make the Young's modulus of the second solid electrolyte layer 32 greater than that of the first solid electrolyte layer 31, the content of the binder in the second solid electrolyte layer 32 is preferably less than that in the first solid electrolyte layer 31, and is, for example, in the range of 0.1% by weight to 10% by weight.

[0028] The thickness of the second solid electrolyte layer 32 is, for example, in the range of 3 μm to 135 μm from the viewpoint of achieving a satisfactory volumetric capacity density and insulating properties of the battery, and is preferably, for example, in the range of 15 μm to 30 μm from the viewpoint of reducing the size of the battery. It is preferable that second solid electrolyte layer 32 has a thickness such that the ratio of the thickness of first solid electrolyte layer 31 to the total thickness of solid electrolyte layer 30 formed from first solid electrolyte layer 31 and second solid electrolyte layer 32 satisfies 0.1 to 0.5.

[0029] {Creation of the second solid electrolyte layer} The method for producing the second solid electrolyte layer 32 is not particularly limited, and the layer can be produced by a known method. For example, the materials constituting the second solid electrolyte layer 32 are mixed with a solvent to form a slurry, and the slurry is applied to the surface of a substrate by a wet method such as a doctor blade method, a die coating method, or a gravure method, and then dried to produce the second solid electrolyte layer 32. The substrate can be of the same type as the positive electrode current collector 22.

[0030] {Effect of two solid electrolyte layers} The all-solid-state battery 100 according to the present disclosure, which has the positive electrode 20, the solid electrolyte layer 30 as a separator, and the negative electrode 40, has a first solid electrolyte layer 31 between the negative electrode 40 and the second solid electrolyte layer 32, the first solid electrolyte layer 31 having a smaller Young's modulus than the second solid electrolyte layer 32. Conventional solid electrolyte layers have a small amount of binder, and therefore may crack due to being unable to relieve stress caused by the expansion and contraction of Si in the negative electrode. In addition, the first solid electrolyte layer 31 may have an increased cell resistance if the binder is increased. In addition, the first solid electrolyte layer 31 alone can relieve stress, but due to its softness, it stretches in a direction parallel to the electrodes and creeps (shrinks in a direction perpendicular to the electrodes) caused by constraints, making the first solid electrolyte layer 31 thinner, making it difficult to maintain insulation against unevenness on the positive and negative electrode surfaces and foreign matter mixed in.

[0031] The solid electrolyte layer 30 of the present invention is formed by stacking two solid electrolyte layers, the second solid electrolyte layer 32 having a small amount of binder and being resistant to deformation, and the first solid electrolyte layer 31 serving as a stress relaxation layer and having a smaller Young's modulus than the second solid electrolyte layer 32, thereby reducing the stress applied to the second solid electrolyte layer 32 and suppressing cracking of the solid electrolyte layer. Furthermore, deterioration of the interfacial contact between the solid electrolyte layer and the positive and negative electrode layers can be suppressed, and a voltage drop during self-discharge can be suppressed.

[0032] <Negative electrode> The negative electrode 40 has a negative electrode current collector 42 and a negative electrode layer 41 formed on the negative electrode current collector 42, and is disposed in contact with the first solid electrolyte layer 31. Note that, although the negative electrode layer 41 is disposed only on one side between the negative electrode current collector 42 and the first solid electrolyte layer 31 in FIG. 1, it may be formed on both sides of the negative electrode current collector 42.

[0033] {Negative electrode layer} The negative electrode layer 41 includes at least a negative electrode active material. The negative electrode active material may be a known negative electrode active material applicable to all-solid-state batteries. For example, silicon-based active materials such as Si and Si alloys, carbon-based active materials such as graphite and hard carbon, various oxide-based active materials such as lithium titanate, lithium metal, lithium-based active materials such as lithium alloys, etc. may be used. The particle size of the negative electrode active material is not particularly limited, but is in the range of 5 to 50 μm, for example. The content of the negative electrode active material in the negative electrode layer 41 is in the range of 30% by weight to 90% by weight, for example.

[0034] The negative electrode layer 41 may optionally include a solid electrolyte. The solid electrolyte may be the same type as the solid electrolyte used in the positive electrode layer 21. The content of the solid electrolyte in the negative electrode layer 41 is not particularly limited, but is, for example, in the range of 10% by weight to 70% by weight.

[0035] The negative electrode layer 41 may optionally contain a conductive assistant. The conductive assistant may be the same type as the conductive assistant used in the positive electrode layer 21. The content of the conductive assistant in the negative electrode layer 41 is not particularly limited, but is, for example, in the range of 0.1% by weight to 20% by weight.

[0036] The negative electrode layer 41 may optionally include a binder. The binder may be of the same type as the conductive assistant used in the positive electrode layer 21. The content of the binder in the negative electrode layer 41 is not particularly limited, but is, for example, in the range of 0.1% by weight to 10% by weight.

[0037] The thickness of the negative electrode layer 41 is not particularly limited and may be appropriately set according to the desired battery performance, for example, in the range of 0.1 μm to 1 mm.

[0038] {Negative electrode current collector} The negative electrode current collector 42, which collects the current of the negative electrode active material contained in the negative electrode layer 41, may be made of a metal foil, a metal mesh, or the like. Metal foil is particularly preferable. Examples of metals constituting the negative electrode current collector 42 include stainless steel, aluminum, nickel, iron, copper, titanium, and carbon. The thickness of each of the negative electrode current collectors 42 is not particularly limited and may be the same as that of a conventional negative electrode current collector. For example, it is in the range of 0.1 μm to 1 mm.

[0039] {Preparation of negative electrode} The method for producing the negative electrode 40 is not particularly limited, and the negative electrode 40 can be produced by a known method. For example, the material constituting the negative electrode layer 41 is mixed with a solvent to form a slurry, and the slurry is applied to the surface of the negative electrode current collector 42 (which may be the first solid electrolyte layer 31) as the base material by a wet method such as a doctor blade method, a die coating method, or a gravure method, and then dried to produce the negative electrode 40.

[0040] <Fabrication of all-solid-state battery (battery assembly)> The method for producing the all-solid-state battery 100 is not particularly limited, but the all-solid-state battery 100 can be produced by laminating the positive electrode 20, the solid electrolyte layer 30, and the negative electrode 40 so that the solid electrolyte layer 30 formed by the first solid electrolyte layer 31 and the second solid electrolyte layer 32 is disposed between the positive electrode 20 and the negative electrode 40, and then housing the resultant in an exterior body such as a laminate film. For example, a production method may be mentioned in which the positive electrode 20 is superimposed and pressed onto the second solid electrolyte layer 32, the negative electrode 40 is superimposed and pressed onto the first solid electrolyte layer 31, the base materials attached to the second solid electrolyte layer 32 and the first solid electrolyte layer 31 are peeled off, and the first solid electrolyte layer 31 is superimposed and pressed onto the second solid electrolyte layer 32.

[0041] The positive electrode 20 having the second solid electrolyte layer 32 superimposed thereon and the negative electrode 40 having the first solid electrolyte layer 31 superimposed thereon are separately pressed and then bonded together, whereby the entire all-solid-state battery is densified and an all-solid-state battery can be produced in a bonded state.

[0042] {Exterior body} The exterior body may be a known laminate film that can be used for an all-solid-state battery, such as a resin laminate film, a resin laminate film on which a metal is vapor-deposited, or a metal laminate film such as aluminum. EXAMPLES

[0043] [Fabrication of all-solid-state batteries] A total of nine types of test all-solid-state batteries (all-solid-state lithium ion secondary batteries) of Examples 1 to 8 and Comparative Example 1 were produced by the production method described below.

[0044] Example 1 <Preparation of positive electrode> The positive electrode active material is LiNi with a particle size of 6 μm. 1 / 3 Mn 1 / 3 Co 1 / 3 Using O2 powder, the surface of the positive electrode active material was coated with LiNbO3 by the sol-gel method. Specifically, equimolar amounts of LiOC2H5 and Nb(OC2H5)5 were dissolved in an ethanol solvent to prepare a metal alkoxide liquid for coating. Then, the metal alkoxide liquid for coating was coated on the surface of the positive electrode active material using a rolling fluidized coating device (model: SFP-01, product of Powrex Corporation) under atmospheric pressure. At that time, the treatment time was adjusted so that the thickness of the coating film was approximately 5 nm. Next, the coated positive electrode active material was heat-treated at 350°C under atmospheric pressure for 1 hour to obtain LiNiO3-coated LiNb ... 1 / 3 Mn 1 / 3 Co 1 / 3 A positive electrode active material consisting of O2 was obtained.

[0045] A positive electrode was fabricated using the positive electrode active material obtained above and 15LiBr·10LiI·75(0.75Li2S·0.25P2S5) glass ceramics with a particle size of 2.5 μm as a sulfide solid electrolyte. Specifically, the positive electrode active material and the sulfide solid electrolyte were weighed out so that the weight ratio of the positive electrode active material:sulfide solid electrolyte was 75:25, and 4 parts of a PVDF-based binder and 6 parts of acetylene black as a conductive assistant were weighed out for 100 parts of the positive electrode active material, and these were mixed with butyl butyrate so that the solid content was 70% by weight, and kneaded with a stirrer to obtain a composition for forming a positive electrode layer (hereinafter also referred to as a positive electrode paste). Next, the obtained positive electrode paste was applied by blade coating using an applicator to a positive electrode current collector made of aluminum foil with a thickness of 15 μm in a basis weight of 25 mg / cm. 2 The coating was then dried at 120° C. for about 3 minutes to obtain a positive electrode in which a positive electrode layer was formed on a positive electrode current collector made of aluminum foil.

[0046] <Preparation of negative electrode> A negative electrode was produced using Si powder with a particle size of 6 μm as the negative electrode active material and the same sulfide solid electrolyte as the positive electrode as the solid electrolyte. Specifically, the negative electrode active material and the sulfide solid electrolyte were weighed out so that the weight ratio of the negative electrode active material:sulfide solid electrolyte was 55:45, and 6 parts of a PVDF-based binder and 6 parts of acetylene black as a conductive assistant were weighed out for 100 parts of the negative electrode active material, and these were mixed with butyl butyrate so that the solid content was 70% by weight, and kneaded with a stirrer to obtain a composition for forming a negative electrode active material layer (hereinafter also referred to as a negative electrode paste). Next, the obtained negative electrode paste was applied by blade coating using an applicator to a negative electrode current collector made of copper foil with a thickness of 15 μm in a basis weight of 5.6 mg / cm. 2 The coating was then dried at 120° C. for about 3 minutes to obtain a negative electrode in which a negative electrode active material layer was formed on a negative electrode current collector made of copper foil.

[0047] <Preparation of the first solid electrolyte layer (stress relaxation layer)> The sulfide solid electrolyte used in the preparation of the positive electrode and the negative electrode was used to prepare a first solid electrolyte layer (stress relaxation layer). Specifically, 98.7 parts by weight of sulfide solid electrolyte and 1.3 parts by weight of SBR binder (volume ratio 97 / 3) were weighed out, mixed with butyl butyrate to give a solid content of 70% by weight, and ultrasonically dispersed for about 2 minutes using an ultrasonic dispersion device (model: UH-50, manufactured by SMT Corporation) to obtain a composition for forming a first solid electrolyte layer (hereinafter also referred to as a first solid electrolyte layer paste). Next, the obtained first solid electrolyte layer paste was applied to an aluminum foil having a thickness of 15 μm in a weight amount of 2.0 mg / cm by the same operation as that for producing the positive electrode described above. 2 The coating was applied uniformly to a thickness of 10 μm. The coating was then naturally dried and further dried at 120° C. for about 3 minutes to produce a first solid electrolyte layer on one surface of the aluminum foil.

[0048] <Preparation of the second solid electrolyte layer> A second solid electrolyte layer was prepared using the sulfide solid electrolyte used in the preparation of the positive electrode and the negative electrode. Specifically, 97.5 parts by weight of sulfide solid electrolyte and 2.5 parts by weight of PVDF-based binder (volume ratio 97 / 3) were weighed out, mixed with butyl butyrate to give a solid content of 70% by weight, and ultrasonically dispersed for about 2 minutes using an ultrasonic dispersion device (model: UH-50, manufactured by SMT Corporation) to obtain a composition for forming a second solid electrolyte layer (hereinafter also referred to as a second solid electrolyte layer paste). Next, the obtained second solid electrolyte layer paste was applied to an aluminum foil having a thickness of 15 μm in a weight amount of 4.0 mg / cm by the same operation as that for producing the positive electrode described above. 2 The coating was applied uniformly to a thickness of 20 μm. The coating was then naturally dried and further dried at 120° C. for about 3 minutes to produce a second solid electrolyte layer on one side of the aluminum foil.

[0049] <Fabrication of all-solid-state battery (battery assembly)> The second solid electrolyte layer was punched out together with the aluminum foil into a 3 cm x 3 cm square shape, and the positive electrode punched out in the same shape was placed on the second solid electrolyte layer, and a pressure of 1 ton / cm was applied. 2Next, the first solid electrolyte layer (stress relaxation layer) was punched out together with the aluminum foil into a square shape of 3 cm x 3 cm, and the negative electrode punched out in the same shape was placed on the first solid electrolyte layer, and pressed with a pressure of 1 ton / cm. 2 The aluminum foil attached to the first solid electrolyte layer and the second solid electrolyte layer was then peeled off, and the first solid electrolyte layer was placed on the second solid electrolyte layer, and pressed with a pressure of 3 tons / cm. 2 The sample was pressed at a pressing pressure of 1000 MPa. The laminated electrode assembly thus obtained was sealed in an exterior body made of an aluminum laminate film to which a positive electrode terminal and a negative electrode terminal were previously attached, to produce a test all-solid-state battery of Example 1.

[0050] Example 2 A test all-solid-state battery of Example 2 was produced using the same materials and processes as in Example 1, except that in the preparation of the first solid electrolyte layer paste, the compounding ratio was 95.5 parts by weight of the sulfide solid electrolyte and 4.5 parts by weight of the SBR-based binder (volume ratio 90 / 10).

[0051] Example 3 A test all-solid-state battery of Example 3 was produced using the same materials and processes as in Example 1, except that in the preparation of the first solid electrolyte layer paste, the compounding ratio was 90.4 parts by weight of the sulfide solid electrolyte and 10.6 parts by weight of the SBR-based binder (volume ratio 80 / 20).

[0052] Example 4 A test all-solid-state battery of Example 4 was produced using the same materials and processes as in Example 1, except that in the preparation of the first solid electrolyte layer paste, the compounding ratio was 84.6 parts by weight of the sulfide solid electrolyte and 15.4 parts by weight of the SBR-based binder (volume ratio 70 / 30).

[0053] Example 5 A test all-solid-state battery of Example 5 was produced using the same materials and processes as in Example 1, except that in the preparation of the first solid electrolyte layer paste, the compounding ratio was 77.9 parts by weight of the sulfide solid electrolyte and 22.1 parts by weight of the SBR-based binder (volume ratio 60 / 40).

[0054] Example 6 In the preparation of the first solid electrolyte layer and the second solid electrolyte layer, the weight of the second solid electrolyte layer was 5.4 mg / cm 2 (thickness 27 μm), the weight of the first solid electrolyte layer is 0.6 mg / cm 2 A test all-solid-state battery of Example 6 was produced using the same materials and processes as in Example 3, except that the coating was uniformly applied to a thickness of 3 μm.

[0055] Example 7 In the preparation of the first solid electrolyte layer and the second solid electrolyte layer, the weight of the second solid electrolyte layer was 5.0 mg / cm 2 (thickness 25μm), the weight of the first solid electrolyte layer is 1.0mg / cm 2 A test all-solid-state battery of Example 7 was produced using the same materials and processes as in Example 3, except that the coating was uniformly applied to a thickness of 5 μm.

[0056] Example 8 In the preparation of the first solid electrolyte layer and the second solid electrolyte layer, the weight of the second solid electrolyte layer was 3.0 mg / cm 2 (Thickness 15μm), weight of the first solid electrolyte layer is 3.0mg / cm 2 A test all-solid-state battery of Example 8 was produced using the same materials and processes as in Example 3, except that the coating was uniformly applied to a thickness of 15 μm.

[0057] Comparative Example 1 In the preparation of an all-solid-state battery, the first solid electrolyte layer was not used, and the weight of the second solid electrolyte layer was 6.0 mg / cm 2 A test all-solid-state battery of Comparative Example 1 was produced using the same materials and processes as in Example 1, except that the coating was uniformly applied to a thickness of 30 μm.

[0058] [evaluation] Cell resistance measurements and self-discharge evaluations are performed for the all-solid-state batteries of Examples 1 to 8 and Comparative Example 1. Hereinafter, constant current constant voltage charge is referred to as CCCV charge, constant current constant voltage discharge is referred to as CCCV discharge, and constant current discharge is referred to as CC discharge.

[0059] <Test 1: Cell resistance measurement> After each test all-solid-state battery was restrained to a fixed size in the lamination direction of the electrode body at 100 MPa, it was charged and discharged at 4.5 V-CCCV, current rate 15 mA, current cut 1 mA, and discharged at 4.0 V-CCCV, current rate 15 mA, current cut 1 mA, and left for 1 hour. It was then discharged at CC, current rate 100 mA, current cut 10 seconds, and the cell resistance was measured according to Ohm's law.

[0060] <Test 2: Self-discharge evaluation> After completing Test 1, each test solid-state battery was charged and discharged 10 times at 4.5 V-CCCV charging, a current rate of 15 mA, and a current cut of 1 mA, and discharged at 2.5 V-CCCV discharging, a current rate of 15 mA, and a current cut of 1 mA. After charging at 4.5 V-CCCV charging, a current rate of 15 mA, and a current cut of 1 mA, the difference in voltage after being left for 24 hours and after being left for 48 hours was determined as the self-discharge voltage.

[0061] For the all-solid-state batteries of Examples 1 to 8 and Comparative Example 1, the configurations of the first solid electrolyte layer and the second solid electrolyte layer, the ratio of the thickness of the first solid electrolyte layer to the total thickness of the solid electrolyte layers, the cell resistance measurement results, and the self-discharge voltage measurement results are shown in Table 1. The cell resistance measurement results and the self-discharge voltage measurement results are shown as ratios (%) relative to Comparative Example 1.

[0062] [Table 1]

[0063] FIG. 2 shows the results of cell resistance measurement and self-discharge evaluation when Examples 1 to 8 are compared with Comparative Example 1, where FIG. 2(a) shows the relationship with respect to the binder amount of the first solid electrolyte layer, and FIG. 2(b) shows the relationship with respect to the total thickness of the solid electrolyte layer.

[0064] [result] 2, it was confirmed that when the ratio of the first solid electrolyte layer to the total thickness of the solid electrolyte layer formed from the first solid electrolyte layer and the second solid electrolyte layer is 0.1 to 1.0, and when the amount of the SBR binder in the first solid electrolyte layer is 3 to 40% by weight, the voltage drop due to self-discharge is suppressed. Also, considering the tradeoff of increasing cell resistance, it can be said that the amount of the SBR binder in the first solid electrolyte layer is preferably 30% by weight or less. [Explanation of symbols]

[0065] 20 positive electrode 21 Positive electrode layer 22 Positive electrode current collector 30 Solid electrolyte layer 31 First solid electrolyte layer 32 Second solid electrolyte layer 40 negative electrode 41 Negative electrode layer 42 Negative electrode current collector 60 Electrode body 100 solid state battery

Claims

[Claim 1] An all-solid-state battery in which a negative electrode, a solid electrolyte layer, and a positive electrode are laminated in this order, The negative electrode includes a negative electrode active material and a sulfide solid electrolyte, The positive electrode contains a positive electrode active material and the same sulfide solid electrolyte as the negative electrode, the solid electrolyte layer contains the same sulfide solid electrolyte as the positive electrode and the negative electrode, The solid electrolyte layer is a first solid electrolyte layer adjacent to the negative electrode and further including an SBR-based binder; a second solid electrolyte layer located between the first solid electrolyte layer and the positive electrode, the second solid electrolyte layer further including a PVDF-based binder; a ratio of the binder to the sulfide solid electrolyte contained in the first solid electrolyte layer is made larger than a ratio of the binder to the sulfide solid electrolyte contained in the second solid electrolyte layer, so that the first solid electrolyte layer has a smaller Young's modulus than the second solid electrolyte layer.

Citation Information

Patent Citations

  • All-solid lithium secondary battery

    JP2009301959A

  • Lithium ion secondary battery

    JP2011129316A

  • Solid electrolyte battery, electrode assembly, composite solid electrolyte, and method for manufacturing solid electrolyte battery

    JP2016219130A

  • Negative electrode for all-solid battery

    JP2017054720A

  • All-solid-state battery

    JP2017152324A